Dampak debt to equity ratio dan debt to asset ratio terhadap kinerja keuangan - Hertina, Dede; Pristia Amary, Zalfa Bhetari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of Debt to Equity Ratio and Debt To Asset Ratio on the company's financial performance. The research was conducted on the Consumer Goods Industry company of the Cosmetics and Household Goods Sub-sector listed on the Indonesia Stock Exchange in 2017-2021. The population and sample of this study found 7 companies. This analysis method uses descriptive method, the data used is secondary data obtained from financial statements. The data analysis technique was carried out with the classical assumption testing stage and multiple linear regression analysis. The results show that the Debt to Equity Ratio and Debt to Asset Ratio have a simultaneous effect on Financial Performance in the Cosmetics and Household Goods Sub-Sector listed on the Indonesia Stock Exchange during 2017-2021. The results of the analysis show that partially the Debt to Asset Ratio has no effect on Financial Performance, while the Debt to Equity Ratio has an effect on Financial Performance in the Cosmetics and Household Goods Sub-Sector listed on the Indonesia Stock Exchange during 2017–2021.